The Conditions and Specifications of the Legal Residence for the Wife in the Iraqi Personal Status Law and Islamic Jurisprudence - Suleiman, Nawzad S.; Jawad, Dilshad M. (Mitanni Journal of Humanitarian Sciences, 2023)
This research sheds light on the most important conditions and specifications that must exist in the wifes residence during the existence of the marital bond and after the dissolution of the marriage contract or death or after the wife becomes a foreigner after the end of the waiting period or during the custody of the divorced wife for her son from the husband.Husband and wife arise because of the marriage cntract,and at the same time there are rights and becomes an obligation at the same time to extinguish the marriage contract and failure to implement obligations leads to problems in the family ane is a reason for splitting or divorce in some cases. The wifes acases to a home that fulfills all the basic conditions and specifications of financial rights. For the wife during the existence of the marital relatioship and until it ends bydeath or divorce and until the end of the waiting period or the end of the chils custody period and the Iraq and Kurdistan Personal Identity Law is devoid of a legal text to address this issue in the event of a dispute in it and for the courts to refer in the absence of the legal text to Islamic jurisprudence leads to the issuance of Different decisions on the subject of the dispute due to the different opinions of jurisprudence on the subiect of the dispute,as well as the lack of legal culture among wives and husbands in relation. To the issue of the dispute, The conditions and specificatins of the legal home for the wife, and for this research sheds ight on the these conditins and specifications that must be met in the house of the wife in order for it to be a legal residence and at the same time so that the wives konw their rights and demand them in the gourts.The establishment of a marital relationship or after the divorce or during the custody of the divrced wife to her son.